Sensory innervation of the thoracolumbar fascia in rats and humans - Tesarz, Jonas; Hoheisel, Ulrich; Wiedenhöfer, Bernd; Mense, Siegfried (Neuroscience, 2011)
The available data on the innervation of the thoracolumbar fascia (TLF) are inconsistent and partly contradictory. Therefore, the role of the fascia as a potential source of pain in the low back is difficult to assess. In the present study, a quantitative evaluation of calcitonin gene-related peptide (CGRP) and substance P (SP)-containing free nerve endings was performed in the rat TLF. A preliminary non-quantitative evaluation was also performed in specimens of the human TLF. The data show that the TLF is a densely innervated tissue with marked differences in the distribution of the nerve endings over the fascial layers. In the rat, we distinguished three layers: (1) Outer layer (transversely oriented collagen fibers adjacent to the subcutaneous tissue), (2) middle layer (massive collagen fiber bundles oriented obliquely to the animal's long axis), and (3) inner layer (loose connective tissue covering the paraspinal muscles). The subcutaneous tissue and the outer layer showed a particularly dense innervation with sensory fibers. SP-positive free nerve endings—which are assumed to be nociceptive—were exclusively found in these layers. Because of its dense sensory innervation, including presumably nociceptive fibers, the TLF may play an important role in low back pain.
Gesehen am 27.10.2022